Radiosensitivity enhancement of human thyroid carcinoma cells by the inhibitors of histone deacetylase sodium butyrate and valproic acid - Perona, Marina (2018)
Fil: Perona, Marina. Comisión Nacional de Energía Atómica. Departamento de Radiobiología; Argentina